(untitled) (Conferencea, 2022)
In the new development strategy of Uzbekistan, approved by the Decree of the President of the Republic of Uzbekistan No. PF-60 dated January 28, 2022, 70 bln. Attracting foreign investments in the amount of US dollars will increase the turnover of the country’s stock market to the current 200 mln. 7 billion from US dollars.